Zinc oxide nanoparticles provide an adjuvant effect to ovalbumin via a Th2 response in Balb/c mice. (13th November 2013) - Roy, Ruchi; Kumar, Sandeep; Verma, Alok K.; Sharma, Akanksha; Chaudhari, Bhushan P.; Tripathi, Anurag; Das, Mukul; Dwivedi, Premendra D.
Abstract : ZnO nanoparticles are adjuvants for T-cell-dependent antigen-specific responses Abstract: Zinc oxide nanoparticles (ZNPs) have been used in dietary supplements and may cause an immunomodulatory effect. The present study investigated the effect of ZNPs on antigen-specific immune responses in mice sensitized with the T-cell-dependent antigen ovalbumin (OVA). BALB/c mice were intraperitoneally administered ZNPs (0.25, 0.5, 1 and 3mg) once, in combination with OVA, and the serum antibodies, splenocyte reactivity and activation of antigen-presenting cells were examined. The serum levels of OVA-specific IgG1 and IgE were found significantly enhanced by treatment with ZNPs over control. An increased level of IL-2, IL-4, IL-6, IL-17 and decreased level of IL-10 and TNF-α in splenocytes administered with ZNPs were observed in comparison with control. The ZNPs and OVA-stimulated T lymphocytes showed enhanced proliferation compared with control. Macrophages and B cells showed high expression of MHC class II, whereas higher expression of CD11b in macrophages of the ZNPs and ZNPs/OVA treated groups was observed. The lungs and spleen had increased eosinophils and mast cell numbers. Also, myeloperoxidase activity in lungs was found to be increased by 2.5-fold in the case of ZNPs and 3.75-fold increase in ZNPs/OVA, whereas in intestine, there was significant increase in both the groups. Increased expression of the genes for GATA-3, SOCS-3, TLR-4, IL-13 and IL-5 in the intestine was observed. Collectively, these data indicate that systemic exposure to a single administration of ZNPs could enhance subsequent antigen-specific immune reactions, including the serum production of antigen-specific antibodies, and the functionality of T cells.